Menyuarakan Keseimbangan - Anwar, Muh. Samsul; Arifin, M. Hafizul; Wahyudi, Johan (The International Journal of Pegon : Islam Nusantara civilization, 2025)
Penelitian ini mengulas tentang dakwah wasatiyyah yang dilakukan oleh Tuan Guru Kiyai Haji Muhammad Zainuddin Abdul Madjid (selanjutnya Tuan Guru Zainuddin) (1898-1997), diimplementasikan dalam penguatan pemahaman Islam Wasatiyyah yang beliau dirikan bersama murid-muridnya. Penelitian ini menggunakan metode kualitatif dengan studi kepustakaan yang bersumber dari buku wasiat dan sya’ir karangan Tuan Guru Zainuddin langsung, dan buku-buku lain yang terkait. Teori yang digunakan dalam penelitian ini di antaranya teori wasatiyyah, oleh Quraish Shihab yang mengatakan sesuatu itu bisa dikatakan wasat ketika ada unsur kebaikan di dalamnya dan memberikan manfaat, terbaik dari apa yang baik-baik, adil atau meletakkan sesuatu pada tempatnya, tidak condong kiri ataupun kanan (berada ditengah- tengah). Kedua, teori fungsional struktural, oleh Talcott Parson yang menyatakan sebuah struktur akan berjalan baik jika fungsi-fungsi yang lain berjalan dengan tepat. Ketiga, teori sunstainability, oleh Meadows, et.al, yang menyatakan keberlanjutan dalam sebuah rencana akan terjadi ketika seseorang mampu merespon kebutuhan sosial yang ada, dan respon itu diperuntukkan untuk kebutuhan masa kini dan masa yang akan datang. Ditemukan juga eksistensi dakwah sampai saat ini karena sikaf wasatiyaah yang diterapkan di dalamnya, memanfaatkan fungsi yang ada serta sangat responsif terhadap lingkungan sosial sekitar. This study discusses how wasatiyyah preaching carried out by Tuan Guru Kiyai Haji Muhammad Zainuddin Abdul Madjid (hereinafter referred to as Tuan Guru Zainuddin) (1898-1997) was implemented in strengthening the understanding of Islam Wasatiyyah, which he established together with his students. This study employs a qualitative method with a literature review sourced from the will and poems written by Tuan Guru Zainuddin himself, as well as other relevant books. The theories used in this study include the theory of wasatiyyah, by Quraish Shihab, which states that something can be said to be wasat when it contains elements of goodness and provides benefits, is the best of what is good, is fair, or puts things in their proper place, without leaning to the left or right (being in the middle). Second, the structural functional theory, by Talcott Parson, which states that a structure will function well if all other functions are functioning properly. Third, the theory of sustainability, by Meadows, et.al, which states that sustainability in a plan will occur when someone is able to respond to existing social needs, and that response is intended for the needs of the present and the future. The results of this study conclude that Mr. Zainuddin optimises the function of the madrasah in his series of sermons. It was also found that there are three wasatiyyah sermons in strengthening the function of preaching, which succeeded in establishing a community organisation and providing the first special madrasah for women in NTB. It was also found that the existence of dakwah persists to this day due to the application of the wasatiyyah approach, which leverages existing functions and is highly responsive to the surrounding social environment.